The Relationship Between Soil-transmitted Helminth Infections and Clean and Healthy Living Behavior - Anifa Chofsoh Zuchaliya; Yulia Sari; Sigit Setyawan; Yusuf Ari Mashuri (Universitas Ahmad Dahlan, 2021)
Background: Soil-transmitted Helminth (STH) are nematodes that can infect humans through direct contact with soil due to poor hygiene behavior. School-age children are the most susceptible to the infection. The clinical symptoms of STH infection are usually asymptomatic. However, it can affect the quality of life of the infected. This study aims to analyze the relationship between STH infection with clean and healthy living behavior; Method: This study takes the form of analytic observational research with a cross-sectional approach. The sampling technique used was the total sampling method with subjects of 132 students of Sekolah Dasar (SD) 1 Talakbroto, SD 1 Kedunglengkong, and SD Wates, Simo, Boyolali. The data were obtained from the results of the students' clean and healthy living behavior questionnaire and the examination of stool samples using the Kato Katz technique. Data were presented in a categorical form and analyzed using the chi-square method.; Results: There were 15 students (11%) infected by STH from 132 subjects studied. Based on the chi-square test, the p-value of STH infection and clean and healthy living behavior was 0.043 (p<0,05); Conclusion: There is a significant relationship between STH infection with clean and healthy living behavior.Â